Cumulative incidence of shoulder region tendon injuries in male former elite athletes - Kettunen, J. A.; Kujala, U.; Sarna, S.; Kaprio, J. (International Journal of Sports Medicine, 2011)
Some types of sports are thought to include a high risk for shoulder region tendon injuries but little data exist on long-term cumulative incidence of these injuries. The aim of our study was to investigate shoulder region tendon injuries diagnosed by physicians in former elite male athletes participating in sports including maximal overhead manoeuvres (overhead athletes) and also other athletes before the age of 45 years and within the subjects' lifetime, compared to control subjects. A postal questionnaire was sent in 2002 to male former elite athletes (n=785; mean age 68 years when responding to the questionnaire; overhead athletes n=111, others n=674) and control subjects (n=416; mean age 67 years). Overhead athletes had a higher risk for shoulder region tendinopathy before the age of 45 (adjusted odds ratio (OR) 4.1, 95% confidence interval (CI) 2.0-8.4, p<0.001) and within lifetime (OR 1.8, 95% CI 1.1-3.0, p=0.027) compared to control subjects. Compared to controls the risk for tendon rupture before the age of 45 (adjusted OR 4.4, 95% CI 1.3-14.8, p=0.016) and within lifetime (OR 2.0, 95% CI 1.0-6.9, p=0.041) was also high in overhead athletes. There was no difference in the risks of shoulder region tendon injuries between the other athletes and the control subjects. Our data indicate that shoulder region injuries are common in athletes participating in sports including maximal overhead manoeuvres and the long-term consequences of these injuries for athletes' daily life and functional ability should be determined.